An Assessment of Sustainable Energy-efficient Strategies for Retrofitted Building Development in Abuja, Nigeria - V. C. Nnodu; M. E. Obiegbu; P. S. U. Eneche (Archives of Current Research International, 2017)
Building and construction designs are expected to be smart; characterized with less negative environmental impacts and are to be more or less economically sustainable. In the face of changing climate and thermal discomfort among urban residents, developing energy-efficient structures is imminent. The brunt of this study therefore was to identify sustainable energy-efficient strategies for the retrofitting of buildings in Gwarinpa District of Abuja. This study was however delimited to the development initiatives for energy-efficient buildings, in particular, residential and commercial buildings such as hotels and recreational centres. The research made use of 300 structured questionnaires and a couple of interview sessions with 36 officials from building, planning and energy saving companies and parastatals, while simple tables, Likert scale and Chi-square test were used to analyse the data generated. The result revealed that majority of the officials interviewed in the study area have HND/MED/BSc as their highest qualification (50%), with 5-10 years experience working with building regulations (50%). Also, it was revealed that the mounting of solar energy devices was rated as the highest strategy employed in the study area to ensure an energy-efficient building (with a Likert scale value of 4.4). This is immediately accompanied by the strategies of putting off electrical appliances when not in use and the use of more VAC-VCR system instead of using split units and the planting of trees. Furthermore, a chi-square statistic, x2 = 31.41 led to the acceptance of the alternative hypothesis that sustainable energy-efficient strategies for retrofitting buildings in the study area were significant. The study therefore revealed a ready-state for people in Gwarinpa to key-in more into the use of energy-efficient facilities, such as solar devices (which is a clean form of renewable energy) for meeting their daily energy needs. To this end, smart building policies that will reduce energy consumption and thermal discomfort in the face of climate change and global warming are recommended, particularly for other relatively, economically buoyant areas in Abuja.